SPEECH DISORDERS IN NORMAL DEVELOPED CHILDREN - Rimbayeva Ozoda Bazarbayevna; Salamova Feruza (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the processes of speech development in children, as well as the causes of speech defects in children with developmental disorders, and measures to prevent them. The kids are impressionable and curious. Paying attention to them is very good for us and for her future.